ANALISIS FINANSIAL USAHA KERAMBA JARING APUNG DI PERUSAHAAN PERSEORANGAN DOBRO - Suryanto, Dony; Sumartono, Eko (Jurnal AGRISEP, 2016)
This research is intended to know factors influencing fish production, financial performance and business security of private company Dobro. Data which are analyzed including production data (production, feed, seed and worker) for fish production factors analysis, balancing and profit/loss statement 2006 - 2009 for financial performance and business security analysis. The production factors analysis in this research uses regression method with Cobb-Douglas production function approach. The financial performance and business security use financial statement comparison and ratio analysis. Ratios that be researched are liquidity (ratios that be researched are current and quick ratio), solvability (ratios that be researched are total debt to total asset ratio and total debt to equity ratio), efficiency (ratios that be researched are inventory turnover, account receivable turnover, fixed asset turnover and total asset turnover) and profitability ratio (ratios that be researched are gross profit margin, operating profit margin, net profit margin and return on investment). Business security analysis use Altman Z” score to detect company position in Altman area of bankruptcy. The result of this research could be concluded that fish production is simultaneous and individually influenced by feed, seed and worker. Financial analysis shows company liquidity in good condition with positive average growth values. Solvability is also in good condition with negative average growth values. Commonly efficiency and profitability have normal values, but have negative average growth value. Based Altman Z” score, company exists in area which secure from bankruptcy threat.